Development of an API for EDU segmentation - Liu, Qingyi (Nanyang Technological University, 2023)
EDU stands for elementary discourse unit, which is a clause-like structure in a sentence. EDU segmentation, refers to determining the boundaries to split sentences into multiple EDUs. This project aims to experiment and develop EDU segmentation models. The experiments are conducted using the Rhetorical Structure Theory (RST) dataset and the model performance is evaluated using the F1-score based on the token level EDU boundaries.